Correlation between Knowledge Level and Attitudes of Hypertension Patients with Compliance with Taking Hypertension Medication at the Cita Sehat Primary Clinic Jakarta: Sahruldin, Rina Veronica - Sahruldin, Sahruldin; Veronica, Rina (Jurnal Persada Husada Indonesia, 2023)
Hypertension is known as a cardiovascular disease where sufferers have blood pressure above normal. This disease is often called the silent killer because there are no symptoms and unknowingly the sufferer experiences complications in other organs. At the Cita Sehat Pratama Clinic, East Jakarta, in 2019, hypertension was included in the 10 most common diseases. Data from the World Health Organization states that 50% -70% of patients do not comply with prescribed antihypertensive drugs. This study used an analytic method with a cross-sectional approach. The number of samples taken was 160 people and carried out from August to September 2020. The sampling technique used the Purposive Sampling method. Bivariate results showed a significant relationship between the knowledge of hypertensive patients (p-value = 0.0001) and adherence to taking hypertension medication, with OR = 6.919 and attitudes of hypertensive patients (p-value = 0.001) with adherence to taking hypertension medication, with OR = 17,647. Based on the research results, it is suggested to the clinic to make a sustainable hypertension patient management program in an effort to treat and improve the quality of life of hypertensive patients